Analysing the gender wage gap using personnel records of a large German company - Christian Pfeifer; Tatjana Sohr (Institute for the Study of Labor (IZA), 2008)
We use monthly personnel records of a large German company to analyse the gender wage gap (GWG). Main findings are: (1) the unconditional GWG is 15 percent for blue-collar and 26 percent for white-collar workers; (2) conditional on tenure, entry age, schooling, and working hours, the GWG is 13 percent for blue-collar as well as for white-collar workers; (3) after additionally controlling for hierarchical levels, the GWG is less than 4 percent for blue-collar and 8 percent for white-collar workers; (4) Oaxaca decompositions reveal that the unexplained part of the GWG is 87 percent for blue-collar workers and 46 percent for white-collar workers; (5) males have larger absolute wage growths than females; (6) the relative GWG gets larger with tenure for blue-collar but smaller for white-collar workers; (7) individual absenteeism has no significant impact on the GWG; (8) the gender gap in absenteeism is between 26 and 46 percent. Overall, the results are consistent with statistical discrimination explanations of the gender wage gap, though we cannot rule out other forms of discrimination. A simple model within the context of absenteeism and statistical discrimination is offered.
urn:nbn:de:101:1-20080609142
Keywords: J16; 330; Absenteeism; gender; personnel data; statistical discrimination; wage differentials; Frauenarbeitslohn; Lohndifferenzierung; Geschlechterdiskriminierung; Fehlzeit; Geschlecht; Großunternehmen; Arbeitskräfte; Deutschland